Analisis Kebutuhan Mahasiswa terhadap Bahan Ajar Perkuliahan Proposal dan Tata Tulis Ilmiah - Sri Nur Yuliyawati (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
The topics and sub-topics of teaching materials in “Proposal and Tata Tulis Laporan” courses in Building Design Engineering Study Program have not been developed based on the students’ need analysis, whereas teaching materials are essential components in a learning process. For this reason, this study was conducted to describe learning outcomes which are relevant to the courses and to map the students’ needs of the topics and sub-topics of “Proposal and Tata Laporan” courses. In this study, a descriptive method was used with the 2016 Curriculum document as a data source and 32 students as participants. The results of this study are six learning outcomes which are relevant to the “Proposal dan Tata Tulis Laporan” courses and seven topics needed by the students; Proposal, Penulisan Laporan Ilmiah, konvensi Naskah, Plagiarisme dan Pengutipan, Peristilahan ilmiah, Kalimat Ilmiah, serta Presentasi Ilmiah. This study concludes that these topics and sub-topics needed by the students are relevant to the six learning outcomes so that those topics and sub-topics can be used as teaching materials.